2020
DOI: 10.2298/pan2003277l
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and labour market institutions in Europe

Abstract: The aim of this paper is to analyse the effects of flexibility in the labour market on workers? monetary poverty in 15 European countries in the time span 2005-2016. We estimate how the labour market regulation index (LMRI) affects workers? monetary poverty through two empirical exercises: in the first one, we use an autoregressive distributed lag model and, in the second one, the generalized method of moments model. The results suggest that greater flexibility of the labour market is positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Also, most studies use cross-sectional data. To the best of my knowledge, the only exceptions are the studies by Brady et al (2013), who analyse state-level changes in in-work poverty in the US, and the study by Liotti and Rita (2020), who provide a macro-level analyses of 15 European countries.…”
Section: Previous Research On Predictors Of In-work Povertymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, most studies use cross-sectional data. To the best of my knowledge, the only exceptions are the studies by Brady et al (2013), who analyse state-level changes in in-work poverty in the US, and the study by Liotti and Rita (2020), who provide a macro-level analyses of 15 European countries.…”
Section: Previous Research On Predictors Of In-work Povertymentioning
confidence: 99%
“…Furthermore, one cross-national study indicates no signicant eect of EPL (Brady et al 2010). Finally, using longitudinal methods, one study nds that an index of labour market regulation increases in-work poverty, and that this eect is even amplied in times of economic crisis (Liotti and Rita 2020).…”
Section: Previous Research On Predictors Of In-work Povertymentioning
confidence: 99%
“…The study by Hasan et al (2006) showed empirically that solid commitment to the rule of law and policies that facilitate the creation of new enterprises (through less restrictive regulations) are more relevant for growth and poverty reduction than the nature of the political system in the country. Liotti and Canale (2020) found robust evidence that labor market regulation, namely greater flexibility, is positively correlated with greater poverty among employed people in 15 European countries over the 2005–2016 period. Vollmer and Ziegler (2009) argued that due to higher redistributive concerns linked to the population's needs, democracies should produce a higher human development level—taken as a measure of poverty—than autocracy.…”
Section: Poverty Social Spending Institutional and Political Environm...mentioning
confidence: 99%
“…Following this approach, a rising number of studies conclude that the reforms in the labour market that have tried to make it more flexible have had microeconomic and macroeconomic negative consequences, like a higher labour segmentation, a deterioration in the job quality, unsustainable increase in the household consumption and borrowing, a more inegalitarian personal income distribution, the generation of disincentives to innovation and physical and human capital accumulation, negative impact on productivity growth, higher poverty rates, etc. (Alfred Kleinknecht et al 2013;Jason Heyes and Paul Lewis 2015;Mireia Damiani, Fabrizio Pompei, and Andrea Ricci 2016;Tomás Gutierrez-Barbarrusa 2016;Tridico 2017;Brancaccio, Garbellini, and Giammetti 2018;OECD 2018;Liotti and Rosario Rita Canale 2020).…”
Section: Labour Flexibility and Income Inequalitymentioning
confidence: 99%